Several Impacts of Committing Bribery May Lead to Instability in Politics and Economics in the Country - Sitti Rachmawati (Journal of Social Research, 2023)
Corruption has become a major issue worldwide over decades. Corruption is a sign that there is a mishandled of management in a country. Corruption can be defined as the misusage of power which has an aim for taking opportunities. This research uses case study research method. Enhancing anti-corruption education networks is one of the methods to seek out the corruption. Lukito (2016, p.939) suggests that fighting corruption can be done through the education system and the internalization program of anti-corruption culture in the government, the private, and the public sector. Corruption which includes the top-level public state officials can result in significant misleading in the way the government and society perform. Lacking accountability, transparency, and self-organization is one of the essential factors of committing bribery in the country. A needy for funding a campaign party and having low salaries are also several causes to be considered by the government.